2003
DOI: 10.1038/sj.bjc.6600961
|View full text |Cite
|
Sign up to set email alerts
|

Quinazoline-based α1-adrenoceptor antagonists induce prostate cancer cell apoptosis via TGF-β signalling and IκBα induction

Abstract: Previous studies documented the ability of quinazoline-based a1-adrenoceptor antagonists to induce apoptosis in prostate cancer cells via an a1-adrenoceptor-independent mechanism. In this study we investigated the molecular events initiating this apoptotic effect. Since transforming growth factor-b1 (TGF-b1) mediates prostate epithelial cell apoptosis, we hypothesised that the activation of the TGF-b1 pathway underlies the quinazoline-based apoptotic effect in prostate cancer cells. Treatment of the androgenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
106
1
7

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(116 citation statements)
references
References 40 publications
2
106
1
7
Order By: Relevance
“…Several signaling pathways have been identified to explain doxazosin-induced anoikis and cell apoptosis, namely through activation of transforming growth factor-b and InB pathways (Partin et al, 2003). inhibition of protein kinase B/Akt activation (Shaw et al, 2004); induction of death receptor-mediated apoptosis (Garrison and Kyprianou, 2006); increase in Bax expression (Chiang et al, 2005) and reduction in focal adhesion kinase (Walden et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Several signaling pathways have been identified to explain doxazosin-induced anoikis and cell apoptosis, namely through activation of transforming growth factor-b and InB pathways (Partin et al, 2003). inhibition of protein kinase B/Akt activation (Shaw et al, 2004); induction of death receptor-mediated apoptosis (Garrison and Kyprianou, 2006); increase in Bax expression (Chiang et al, 2005) and reduction in focal adhesion kinase (Walden et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Garrison and Kyprianou 9 have shown that doxazosin increased FADD recruitment and subsequent caspase-8 activation, implicating FAS-mediated apoptosis as a mechanism leading to apoptosis in prostate cells. Partin et al 7 have demonstrated that doxazosin treatment resulted in caspase-3 activation within 24 h. Caspase-3 is a crucial enzyme for the executive phase of apoptosis that can be activated after the stimulation of tumor necrosis factor family receptors. Konig et al 26,27 have demonstrated that TNF-a can be one of the key factors in the benign prostate hyperplasia (BPH) pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Many pathways leading to apoptosis within prostate have been proposed. [1][2][3][4][5][6][7][8] The recent results show that doxazosin triggers apoptosis within benign and malignant prostate cells via an imprecisely defined receptor mechanism related to tumor necrosis factor receptors family (TNFRs). [8][9][10][11][12] TNFRs such as CD95 (FAS), TNFR-1, TNFR-2 and CD40 may be responsible for triggering apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that the key identified molecular players of doxazosin action were members of the TGFb pathway such as Smad4 and TGFb1-inducible early gene (TIEG1) (Partin et al, 2003). In particular, increased expression of Smad4 was reported at the protein level 6 h after doxazosin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the quinazoline-based antagonists have been shown to exert potent apoptotic action against benign and malignant prostate cells mediated via transforming growth factor b (TGFb) signaling and activation of NF-kb pathway (Kyprianou and Benning, 2000;Benning and Kyprianou, 2002;Partin et al, 2003). In in vivo experimental models of both prostate cancer and BPH xenografts, doxazosin-induced apoptosis led to suppression of prostate growth without affecting their proliferative ability (Yang et al, 1997;Kyprianou and Benning, 2000).…”
Section: Introductionmentioning
confidence: 99%